miRNAs in secondary hyperparathyroidism: literature review - Ziyi Lu; Kexin Zhang; Junyue Huang; Shoukai Zhang (BMC Nephrology)
Abstract Secondary hyperparathyroidism (SHPT) is a common complication of Chronic kidney disease (CKD), which is mainly manifested by the overproduction of Parathyroid hormone (PTH), leading to multi-system pathologies such as calcium and phosphorus metabolism disorders, skeletal lesions, and cardiovascular diseases, which seriously affects the quality of life of patients. In recent years, the role of microRNAs (miRNAs) in the pathogenesis of SHPT has been gradually revealed, providing new research directions for diagnosing and treating the disease. miRNAs play an important role in the development of SHPT by regulating genes related to calcium-phosphorus metabolism, influencing the stability and translational efficiency of PTH mRNAs, and regulating the proliferation and apoptosis of parathyroid cells. miRNA-based gene therapy strategies (e.g., miRNA antagonists or mimics) have shown promising therapeutic effects in animal models, but their clinical translation still faces challenges such as targeted delivery and safety. This review aims to summarize the mechanistic roles of miRNA and the progress of research in SHPT studies to provide a theoretical basis for diagnosing and treating SHPT.